2018
DOI: 10.3389/fimmu.2018.01578
|View full text |Cite
|
Sign up to set email alerts
|

Immune Landscape of Colorectal Cancer Tumor Microenvironment from Different Primary Tumor Location

Abstract: To define differences in tumor microenvironment (TME) immune phenotypes between right and left colorectal cancers (CRCs) and explore their therapeutic implications. Gene expression profiling and clinical characteristics of patients with CRC were retrieved from The Cancer Genome Atlas data portal. Immune cell infiltration was estimated based on single-sample gene set enrichment analysis. CRCs tissue microarrays (TMAs) containing 90 consecutive cases of surgical samples were used for validation. Expression of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 55 publications
6
114
1
Order By: Relevance
“…The immune landscape of CRC TME comprises of diverse populations that modulate anti-tumor responses. We and others have previously shown accumulation of immunosuppressive myeloid cells and Treg expressing multiple IC in CRC TME [14][15][16]. Moreover, previous studies have reported TIM-3 expression on dysfunctional T cells in various malignancies [17].…”
Section: Cd4 + Tim-3 + T Cells In the Tumor Microenvironment Have Mormentioning
confidence: 79%
“…The immune landscape of CRC TME comprises of diverse populations that modulate anti-tumor responses. We and others have previously shown accumulation of immunosuppressive myeloid cells and Treg expressing multiple IC in CRC TME [14][15][16]. Moreover, previous studies have reported TIM-3 expression on dysfunctional T cells in various malignancies [17].…”
Section: Cd4 + Tim-3 + T Cells In the Tumor Microenvironment Have Mormentioning
confidence: 79%
“…Accumulating researches have highlighted the crucial role of cancer microenvironment in melanoma and CRC progression, metastasis and evasion of the immune surveillance . In this study, we found that the quantity of CAFs in melanoma and CRC were positively correlated with PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the infiltration levels of stromal cells located in tumour microenvironment, the single-sample gene set enrichment analysis (ssGSEA) method was applied using the 'GSVA' package. 23 The marker genes of immune and stromal cells used for ssGSEA were retrieved from the works of Bindea et al 24…”
Section: Characterization Of Tumour Microenvironmentmentioning
confidence: 99%